Designing An IOT-Based Smart Home Control Using Blink Application and ESP8266 Wi-Fi Module - Suwartika, Rini; Den Restu Singgih (Politeknik Dharma Patria Kebumen, 2021)
The very rapid development of technology has a significant impact on human life today. The aids of facilitating human work are starting to be in great demand. Automation of tools is thought to shorten the time, be more accessible and be faster. Smart Home is one's technologies applications needed today. This study aims to designs an IoT-based innovative home prototype. The resulting intelligent home prototype uses the DHT11 sensor at a room temperature detector, the MQ-2 the sensor as a gas leak detector, an ultrasonic sensor as the object detector, the MC38 magnet sensor as door security, a relay as ON or OFF the lamp switch, buzzer as an alarm, and using a microcontroller. A nodemcu with a Wi-Fi module ESP8266 controlled via Blynk App. Research and Development (R & D) method were research method used. It is hoped that the IoT-based Smart Home technology will be provided convenience to its users in everyday life.